(untitled) (Applied Biological Research, 2024)
Eulophia nuda Lindl. corms are used to cure cancer and is overexploited by the traditional medicine practitioners and medicinal plant traders. The corms of Geodorum densiflorum look morphologically similar to the corms of Eulophia nuda, hence it is used as an adulterant to the corms of Eulophia nuda, consequetly, the population of G. densiflorum is also facing the exploitation pressure. In present study, asymbiotic seed germination of both the terrestrial orchids was achieved using six media like Vacin and Went (WV) medium, Malmgren modified (MM) terrestrial orchid medium, modified Kundson C medium, ½ MS medium, Lindemann medium (LM) and BM1 medium along with three photoperiods (0/24, 16/8, and 24/0 h L/D). Eulophia nuda showed highest asymbiotic seed germination on MM medium (80.55 %) and the best light treatment was 0/24 h L/D. The highest asymbiotic seed germination of G densiflorum was on VW (84.07%), LM (83.29%) and BM 1(81.02%) and the best light treatment was 24/0 h L/D.